Scaling Up Physical Activity Promotion Projects on the Community Level for Women in Difficult Life Situations and Older People: BIG-5 and GET-10-A Study Protocol - Maike Till; Karim Abu-Omar; Annika Herbert-Maul; Tobias Fleuren; Anne Kerstin Reimers; Heiko Ziemainz (Frontiers Media S.A., 2022)
IntroductionPhysical inactivity is a major risk factor for a population's health, especially among socially disadvantaged groups. Many health promotion projects focus on increasing physical activity among their respective target groups. However, because they are mostly developed and implemented under laboratory conditions, they fail when being scaled to real-world settings. The community-based participatory research projects BIG and GESTALT have demonstrated their effectiveness regarding the physical activity promotion in real-world settings by employing a participatory method.Material and AnalysisWithin the context of the BIG-5 and GET-10 projects, these previously implemented and tested participatory projects are scaled to 15 additional settings in Bavaria, Germany. By applying an overarching mixed-methods evaluation framework, the aim is to gain insights into a) the recruitment of communities for scale-up; b) the specific results of the projects according to the RE-AIM framework. In the recruitment of communities, standardized information on the first contact, the consultation process, the person in charge, and previously implemented health promotion projects are collected. A systematic web search will complete information on each community and their health promotion activities. Results will be compared with information on those communities most in need, here according to the deprivation index of communities in Bavaria, Germany. The scale-up process and its results will be measured using semi-structured interviews with project coordinators. A standardized questionnaire will be used with the course's participants. Applying the RE-AIM framework, the collected data will be analyzed deductively.DiscussionWe expect the results to be highly relevant for the effective scale-up of any health promotion project. The study will enhance the understanding of how to reach those communities most in need of health promotion projects and will identify the barriers coordinators face in reaching socially disadvantaged groups.ConclusionAlthough participatory projects are often used as individual projects, little is known about the scaling up of participatory health promotion projects. This cross-cutting evaluation of two projects aims at producing data on the barriers and facilitators for the reach of settings most in need, and those success factors for a durable implementation.